The Oxford handbook of innovation management - Dodgson, Mark, 1957-; Gann, David; Phillips, Nelson (Oxford : Oxford University Press, 2013)
While innovation is widely recognised as being critical to organisational success and the well-being of societies, it requires careful management to ensure that innovation processes have the best possible impact. This volume provides a wide range of perspectives on the nature of innovation management and its influences.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on February 26, 2014).
Keywords: Organizational change -- Management; Technological innovations -- Management